Developing School Information Program: Integrated Management System based on Character Value at SMP Negeri 9 Tapung - Muhammad Yahya; Hadion Wijoyo (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research aims to develop a student data management system at 9 Tapung Junior High School (SMP) Negeri 9 Tapung, which has not documented using a computer or school web using text-based programming languages like HTML, JavaScript, CSS, and PHP. The student information system design at SMP Negeri 9 Tapung in its manufacture uses a literacy methodology where each phase can be carries repeatedly until it gets the desired results. The phase of system manufacture is the investigation, analysis, design, and implementation. To make this application, the author uses PHP and MySQL. This development research results create a student information system application that can display school data, student data, which graphics form, and its development, including data on the development of honesty and discipline. The system also displays the student interests and talents observed, extracurricular activities, student violations, and achievement. This application still needs development, refinement, the addition of features, and suggestions, and criticism from all related parties to create a better and structured information system to improve the quality and character of SMP Negeri 9 Tapung.